Circulant weighing matrices whose order and weight are products of powers of 2 and 3 - Schmidt, Bernhard (2013)
We classify all circulant weighing matrices whose order and weight are products of powers of 2 and 3. In particular, we show that proper CW(v,36)ʼs exist for all v ≡ 0 (mod 48), all of which are new.